Dilemmas with surgical intervention in neonates with Necrotizing Enterocolitis without pneumoperitoneum - Boipai, Manika; Gupta, Rahul (Journal of Neonatal Surgery, 2021)
Background: The diagnosis of perforation in the absence of pneumoperitoneum in necrotizing Enterocolitis (NEC) remains difficult. The decision to operate should be taken up during the “golden period” which occurs after the onset of intestinal gangrene, but before intestinal perforation. This study was done to analyse the outcomes of two groups of surgically managed NEC patients based on the radiographic findings (presence or absence of pneumoperitoneum) and compare the actual surgical findings. Methods: A prospective observational study was performed from October 2018 to February 2020. The operated patients of NEC were divided into two groups based on the preoperative presence (Group A) or absence of pneumoperitoneum (Group B). A “p” value of less than 0.05 was considered significant for comparative analysis. Results: There were 81 patients with clinico-radiological signs of NEC during the study tenure; 51 infants underwent surgery. Group A had 35 (69%) and Group B had 16 (31%) patients. In 11/16 (69%) patients of Group B, perforation was detected and 5/16 (31%) had only gangrenous and necrosis of bowel segment. Out of 16 patients (Group B), predictors of NEC like abdominal wall erythema (Modified Bell's stage IIB) were present in 4 (25%), fixed bowel loops (stage IA/IB) 3 (19%), pneumatosis intestinalis (stage IIA) 1(6%), portal venous gas (stage IIB) 1 (6%), and ascites (stage IIIA) 2 (12%) were observed. The complication rate was 77% among patients of Group A and 44% in Group B (p=0.01). Survival was greater (63% vs. 29%) among Group B patients than Group A (p=0.02). Conclusions: The importance of not relying only on the pneumoperitoneum on radiographs; early diagnosis and prompt surgical intervention is emphasized. Surgical indication for NEC should always be based on the patient’s cumulative clinical and radiologic assessment, especially in the absence of pneumoperitoneum to improve survival rates.